Determination of the child's habitual residence according to the Brussels II bis regulation - Rumenov, Ilija (Pravni letopis, 2013)
The childs habitual residence is becoming one of the most important jurisdictional criteria in the area of private international family law. Its adoption as the primary basis of jurisdiction under the Brussels II bis Regulation, confirms its significance. However, even after one hundred years of its first use in the substantive law of the Hague Convention on Guardianship of 1902, two outstanding issues remain. The criterion is still considered a factual concept and, as a consequence, most of the legal sources that deal with private international law have not provided its definition. In recent years, following the A case of 2009, this position has changed because the European Court of Justice stressed that it follows from the need for uniformapplication of Community law and from the principle of equality that the terms of a provision of Community law which makes no express reference to the law of the Member States for the purpose of determining its meaning and scope must normally be given an autonomous and uniform interpretation throughout the European Community. In another case, Rinau, it was affirmed that the guiding principles of the 1980 Hague Convention concerning the interests of children were taken over, in matrimonial matters and matters of parental responsibility, by the Regulation. Advocate General Kokott held in her opinion in the A case that both provisions pursue the aim that abducted children should return immediately to the State in which they had their habitual residence before the unlawful removal. That coordination also makes a uniform understanding of the concept of habitual residence necessary.The article analyses the practice of the Hague Conference of Private International Law and tries to give an insight into the thirty years of implementation of the 1980 Child AbductionConvention and the 1996 Child Protection Convention, and the problems that have emerged from it. This will help in creating a uniform application of this jurisdictional criterion and auniform understanding of the concept of habitual residence. The article also gives comparative insight into the recent emergence of definitions of the habitual residence in the national codifications of the private international law.
Keywords: child; človekove pravice; družinsko pravo; human rights; mednarodne konvencije; mednarodno zasebno pravo; otroci; pravice otrok